EFFECT OF ETHANOLIC EXTRACT OF EMBLICA OFFICINALIS (AMLA) ON PATHOPHYSIOLOGY OF LIVER IN HYPERLIPIDEMIC ALBINO WISTER RATS. - BHEEMSHETTY S. PATIL,; SHANKREPPA D. DESAI,; POTEKAR R M, (International Journal of Pharma and Bio Sciences, 2015)
It has been reported that hyperlipidemia plays central role in the development of atherosclerosis, liver disorders and oxidative stress. Embilica officinalis also known as Amla or Indian Gooseberry acts as antihyperlipidemic, antioxidant and liver tonic. It actively contains tannins, gallic acids and flavonoids. Aims: To evaluate the effect of the Ethonolic extract of Emblica Officinalis on pathophysiology of liver and on biochemical parameters in Hyperlipidimic albino Wister rats. Extraction of Emblica Officinalis by Soxhlet apparatus using 99% ethanol at 60º temp for 24hrs and Phytochemical analysis was done. Group I served as normal control. Group II Fed with Isocaloric diet. Group III Fed with Hyperlipidimic diet. Group IV. (Isocaloric diet 21 days + Embilica Officinalis 21 days). ok(hyperlipidemic diet 21 days+ Embilica Officinalis 21 days). Dose of ethonolic extract of Emblica Officinalis: (100mg/kg b. wt daily). %body weight gain, liver weight and hepatosomatic index were significantly improved in hyperlipidemic rats treated with Amla. There was significant improvement in lipid profile and markers of liver functions. Liver shown fatty changes in hyperlipidemic rats and normal Hepatocytes in Hyperlipidimic rats treated with Amla. It can be concluded that amla may be effective , natural therapeutics in hyperlipidemia and liver disorders.